Comparative study of residual stress prediction methods in additive manufacturing processes - Suyambazhahan Sivalingam; Sunny Narayan; Sakthivel Rajamohan; Ivan Grujic; Nadica Stojanovic (Communications - Scientific letters of the University of Zilina, 2022)
The additive manufacturing (AM) of products involves various processes, such as raising the temperature of a work-piece (part) and substrate to the melting point and subsequent solidification, using a movable source of heat. The work piece is subjected to repeated cycles of heating and cooling. The main objective of this work was to present an overview of the various methods used for prediction of the residual stresses and how their contributions can be used to improve current additive manufacturing methods. These novel methods of manufacturing have several merits, compared to conventional methods. Some of these merits include the lower costs, higher precision and accuracy of manufacturing, faster processing time and more eco-friendly approaches to processes involved.